Comparison of functional and static evaluation tools among adolescent athletes - Paszkewicz, J. R.; McCarty, C. W.; Van Lunen, B. L. (The Journal of Strength and Conditioning Research, 2013)
This study aimed to compare functional movement screen (FMS [TM]) scores and Beighton and Horan joint mobility index (BHJMI) scores among pubescence in adolescent athletes. Sixty-six adolescents between the ages of 8 and 14 voluntarily participated in this study. The participants performed the tests of the BHJMI, the tasks of the FMS (TM), and the clearing tests of the FMS (TM). The composite scores of the FMS (TM) and the BHJMI were scored objectively by the same researcher. The subjects were separated into prepubescent, early-pubescent, and postpubescent groups based on the results of the modified pubertal maturation observational scale. A 2 × 3 (gender × pubescence) factorial analysis of variance revealed a main effect for FMS (TM) scores across pubertal groups (p = 0.032) but not in BHJMI composite scores (pre = 2.69 ± 0.40, pub = 1.96 ± 0.40, post = 3.13 ± 0.43, p = 0.131). The postpubescent participants had significantly higher FMS (TM) scores compared with the prepubescent participants (post = 15.91 ± 0.47, pre = 14.28 ± 0.44, p = 0.008) and the early-pubescent participants (pub = 14.55 ± 0.44, p = 0.039). No differences were identified between gender for FMS (TM) scores (male participants = 15.16 ± 0.38, female participants = 14.67 ± 0.35, p = 0.351) or BHJMI scores (male participants = 2.36 ± 0.35, female participants = 2.83 ± 0.32, p = 0.321). No significant interactions were found between gender and pubescence regarding the BHJMI composite scores (p = 0.503) or the FMS (TM) scores (p = 0.216). There was no correlation between FMS (TM) composite scores and BHJMI composite scores (p = 0.89). Our results suggest that the FMS (TM) can discriminate between levels of pubescence and detect alterations during the pubertal growth cycle, whereas the BHJMI may not. A prospective extension of this study to include follow-up of injured participants appears worthwhile to determine if the FMS (TM) can suitably predict injury in the adolescent population.